'No, I don't know where that is. All I know is my room.': Topographical disorientation and user‐centred requirements for in‐hospital navigation aids of people with dementia and their caregivers. (7th December 2020) - Kowe, Antonia; Goerss, Doreen; Teipel, Stefan J.
Abstract: Background: Hospitals are complex buildings in which the risk of disorientation is high with negative consequences on financial and staff resources due to missed appointments and increased need of support. Existing indoor navigation aids, such as accompanying services, spatial design or technical assistance, often miss the intended users' needs. Based on the value sensitive design approach, this study asked people with dementia (PwD) and their caregivers about the requirements in‐hospital navigation aids should fulfil for them to be considered useful. Method: We conducted semi‐structured interviews with two stakeholder groups of stationary dementia care: PwD (n = 10, agemean = 83, 9 years) and informal caregivers (n = 5, agemean = 73, 8 years). In the interviews, we asked for previous experiences including barriers for the use of existing navigation aids. We analysed underlying values and requirements for improved technologies. The interviews were evaluated using qualitative content analysis according to Mayring. Result: Accompanying services by hospital staff or relatives were considered by respondents to be the most helpful support for in‐hospital orientation. Barriers for the use of existing in‐hospital navigation aids are their low visibility and lacking need of usage due to restricted mobility of in‐patients with dementia. Interestingly, some PwD are willing to use technical assistance for navigation support although their digital competencies are considered to be very low by caregivers. For both stakeholder groups, trust is an important value in technical devices for navigation. PwD highlighted independence as further important value while caregivers prioritized safety. Both respondents groups wanted a device that could be worn on the body and that gave simple instructions for finding rooms via visual or acoustic signals. Conclusion: PwD and caregivers can specify needs for in‐hospital navigation aids and their requirements differ only slightly due to varying values. User‐centred design potentially helps to improve emerging technologies for patient‐centred stationary care.